(untitled) (MIST International Journal of Science and Technology, 2022)
The Padma Multipurpose Bridge (PMB) is one of the biggest megaprojects of Bangladesh connecting one third of the country with the capital city, Dhaka. The infrastructure is expected to produce considerable uplift on the nation’s transport system, the national and regional economy, employment, household income, and ultimately, poverty reduction. From construction and river management points of view, it is the most difficult and engineering innovation-intenstive project in the world. Hence the Padma Multipurpose Bridge (PMB) required analytical, computational and experimental studies. In this work, a 3D Finite Element (FE) model of the actual PMB containing a single (6x150m) 900m modules has been developed in MIDAS Civil, a commercial computer program for bridges. P-y soil spring model following API guideline has been developed to conform flexible support system of the bridge pier. Following BNBC 2020, the bridge’s performance has been evaluated for the 475-year, 975 years, and 2475-year return periods for Service Level, Design Basis and the Maximum Credible Earthquake (MCE), respectively. The forced based design shows that the bridge pier reached only 28% and 36% of its axial and shear capacity respectively for an earthquake return period of 2475 years. On the other hand, the pier has reached a maximum of 41% of its total shear capacity for the same seismic level. MIJST, Vol. 10, November 2022 (Special Issue: Padma Bridge): 57-63